2019
DOI: 10.9734/jgeesi/2019/v20i330105
|View full text |Cite
|
Sign up to set email alerts
|

Geospatial Analysis of Groundwater Quality in Ludhiana, Punjab (India)

Abstract: This paper presents a geospatial analysis of the groundwater quality of Ludhiana, Punjab, India. The groundwater samples were collected from 99 locations using grid based sampling procedure and analysed for parameters viz. pH, total dissolved solids (TDS), total hardness (TH), calcium (Ca2+), magnesium (Mg2+), sodium (Na+), potassium (K+), fluoride (F-), chloride (Cl-), nitrate (NO3-), sulphate (SO24-) and bicarbonate (HCO3-). Sampling was done during both pre-monsoon and post-monsoon periods. Water quality in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Ebri, et al [5] in their investigation of groundwater quality in boreholes with proximity to soak away concluded that siting borehole close to any pollution source (soak away) is very detrimental to the quality of the ground water resources. Singh et al [20] also showed in their research that the quality of groundwater source has deteriorated by human and industrial activities some of which are release of effluent from pits, releases of residential wastewater in defective channels, improper management of sanitary landfills, contaminated industrial sites, industrial discharges and others.…”
Section: Analysis Of Biological Parametersmentioning
confidence: 99%
“…Ebri, et al [5] in their investigation of groundwater quality in boreholes with proximity to soak away concluded that siting borehole close to any pollution source (soak away) is very detrimental to the quality of the ground water resources. Singh et al [20] also showed in their research that the quality of groundwater source has deteriorated by human and industrial activities some of which are release of effluent from pits, releases of residential wastewater in defective channels, improper management of sanitary landfills, contaminated industrial sites, industrial discharges and others.…”
Section: Analysis Of Biological Parametersmentioning
confidence: 99%
“…There are 37,047 (micro, small, and medium) businesses and 151 large-scale businesses which are registered in the study area [32]. Studies have reported increasing groundwater quality deterioration in the study area due to activities such as industrial wastewater disposal, disposal of garbage, use of fertilizers, and pesticides on agricultural land [28].…”
Section: Study Area Descriptionmentioning
confidence: 99%
“…Ludhiana, Punjab, India is a fast-growing industrial hub. The indiscriminate disposal of domestic, agricultural, and industrial waste in the area poses a potential threat to its groundwater [28]. However, no comprehensive evaluation of the groundwater pollution caused by ESEs such as heavy metals and arsenic and its associated health risk assessment has been conducted in the area.…”
Section: Introductionmentioning
confidence: 99%